Characterization of the haematological profile of 21 days of tedizolid in healthy subjects. (17th June 2016) - Lodise, Thomas P.; Bidell, Monique R.; Flanagan, Shawn D.; Zasowski, Evan J.; Minassian, Sonia L.; Prokocimer, Philippe
Abstract : Objectives: Tedizolid is a novel oxazolidinone antibacterial. Oxazolidinones carry concerns for time-dependent myelosuppression. To further explore tedizolid's haematological tolerability, we analysed data from a 21 day study comparing safety and pharmacokinetics of tedizolid and linezolid. Methods: This was a Phase 1 study in healthy volunteers comparing five treatments (each n  = 8) over 21 days: tedizolid at 200, 300 or 400 mg once daily; linezolid at 600 mg twice daily; and placebo. Routine laboratory haematological parameters (platelet, absolute neutrophil, white blood cell, red blood cell and reticulocyte counts) were compared between groups. Adverse haematological outcomes were pre-specified as any parameter below the standard lower limits of normal (LLN), substantially abnormal (<50% LLN for neutrophils; <75% LLN for other parameters) or ≥50% below baseline (platelets only). ClinicalTrials.gov identifier: NCT00671814. Results: During the 21 day study period, pre-specified adverse platelet outcomes were observed in the linezolid ( n  = 2), tedizolid 300 mg ( n  = 1) and tedizolid 400 mg ( n  = 3) groups. Mean platelet counts decreased over time in a dose-dependent manner for tedizolid, with higher doses being similar to linezolid. The magnitude of platelet count decreases from baseline was influenced by unbound drug trough plasma concentrations, which were generally higher in subjects with at least a 20% decrease in platelet count. Substantially abnormal haematological parameters were only observed with linezolid and tedizolid 400 mg. One linezolid and two tedizolid 400 mg subjects discontinued due to meeting criteria for pre-specified adverse haematological outcomes. Conclusions: Although limited to small groups of healthy volunteers, these exploratory results support clinical study of extended treatment durations with tedizolid at 200 mg once daily.